Microstructural and Dynamical Heterogeneity Characteristics in Al2O3- 2SiO2 Liquid - Thi Thanh Ha, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 34 No 1DO - 10.25073/2588-1124/vnumap.4231, 2018)
In this paper the structural and dynamical characteristics in alumina- silicate Al 2 O 3 –2SiO 2 (AS2) liquid are investigated by molecular simulation method. Structural properties are clarified through the pair radial distribution function, distribution of TO n (T= Si, Al) coordination units and distribution of partial bond angle in TO n . Furthermore the change in diffusion mechanism between low and high pressure is revealed by transition of the structural units TO x → TO x±1 . At the low-pressure configuration of the liquid AS2 exhibits the dynamics heterogeneity (DH). The original of dynamic heterogeneity is identified and liquid AS2 consists of separate mobile and immobile regions.